If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 + 3x = 41 Reorder the terms: 6 + 4x + 3x = 41 Combine like terms: 4x + 3x = 7x 6 + 7x = 41 Solving 6 + 7x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7x = 41 + -6 Combine like terms: 6 + -6 = 0 0 + 7x = 41 + -6 7x = 41 + -6 Combine like terms: 41 + -6 = 35 7x = 35 Divide each side by '7'. x = 5 Simplifying x = 5
| -8+x+5-7=20x-10 | | 27.50x+17=23.25x+17 | | 5(4x-3)+8=2 | | 6x+3=-2+11 | | (X-8y+2)*(3x-2c+100)=0 | | -25+(-16)= | | 2(7x+1)=86 | | 76(8686868686868686868686886866888+8)=7 | | 25/60=c/12 | | 7(-2x-3)=-7 | | x(16-x^2)^1/2 | | -10+v-17v=4 | | 24-2x=24 | | -5(-2+x)=25 | | (.5x+5)+[.5(.5x+5)+5]+.75[.5(.5x+5)+5]+5=0 | | b/45=8/9 | | 35=10+4t | | 2y=-19/33 | | a/32=9/16 | | 30=0.75x | | 3(4x-5)+2=4x-11 | | x^2-4x+120=180 | | X/515 | | 6w-11w=20 | | 7x-10=-70+2x | | -15+x-9-6=12x-8 | | 5(l-4)=60 | | -25w=q | | 6z^3-6z=0 | | 3(x-3)+3x=4x+3 | | 6+x=-4x+51 | | 47+6k=3k-2 |